Pentacyclic triterpenes grafted on CD cores to interfere with influenza virus entry: A dramatic multivalent effect. (February 2016) - Xiao, Sulong; Si, Longlong; Tian, Zhenyu; Jiao, Pingxuan; Fan, Zibo; Meng, Kun; Zhou, Xiaoshu; Wang, Han; Xu, Renyang; Han, Xu; Fu, Ge; Zhang, Yongmin; et al.
Abstract: Multivalent effect plays an important role in biological processes, particularly in the specific recognition of virus with its host cell during the first step of infection. Here we report the synthesis of multivalent pentacyclic triterpene grafted on cyclodextrin core and potency of against influenza entry activity. Nine star-shaped compounds containing six, seven and eight pentacyclic triterpene pharmacophore on cyclodextrin scaffold were prepared by way of copper-catalyzed azide-alkyl cycloaddition reaction under microwave activation. Some of the multimers exhibited much potent antiviral activity against H1N1 virus (A/WSN/33), even equivalent or superior to oseltamivir. The most active compound31, a heptavalent oleanolic acid- β -cyclodextrin conjugate, shows an up to 125-fold potency enhancement by its IC50 value over the corresponding monovalent conjugate and oleanolic acid, disclosing a clear multivalent effect. Further studies show that three compounds31 –33 exhibited broad spectrum inhibitory activity against other two human influenza A/JX/312 (H3N2) and A/HN/1222 (H3N2) viruses with the IC50 values at 2.47–14.90 μ M. Most importantly, we found that compound31, one of the best representative conjugate, binds tightly to the viral envelope hemagglutinin with a dissociation constant of K D = 2.08 μ M, disrupting the interaction of hemagglutinin with the sialic acid receptor and thus the attachment of viruses to host cells. Our study might establish a strategy for the design of new pharmaceutical agents based on multivalency so as to block influenza virus entry into host cells. Graphical abstract: Highlights: A series of multivalent pentacyclic triterpene-CD conjugates have been synthesized and characterized. They showed intriguing anti-influenza entry activity. The most active conjugate is compound31 with IC50 at 1.60 µ M. The target of them was confirmed to be the HA protein.